Occurrence of asymptomatic malaria infection and living conditions in the lowlands of Ethiopia: a community-based cross-sectional study - Endale Mengesha Goshu; Meseret Dessalegne Zerefa; Habteyes Hailu Tola (BMC, 2022)
Abstract Background A significant decline in malaria burden was documented in previously high burden African countries. Even though the global decline in malaria burden is significant, about 95% of it was typically found in 29 African countries and the decline was affected by COVID-19 in 2020. The considerable reduction in malaria incidence was noted due to effective prevention and treatment efforts, and rapid changes in living conditions. The relationship between the occurrence of asymptomatic malaria infection and household living conditions is well unstudied. This study aimed to determine the association between household living conditions and the occurrence of asymptomatic malaria in the lowlands of Ethiopia. Methods A community-based cross-sectional study was conducted from January to March 2021 in twelve villages of Gambella, Southern Nation Nationalities and People Region and Afar in Ethiopia. A total of 1366 households were randomly selected, interviewed, and tested for malaria by rapid diagnostic test and blood film microscopic examination. Multiple logistic regression model was used to determine the independent association between living conditions and asymptomatic malaria infection. Results The prevalence of asymptomatic malaria infection among individuals living in dwellings built with traditional floor/wall/roof ranges from 8.1% to 8.4% while it ranges from 2.0% to 4.6% among those living in modern floor/wall/roof houses. Dwellings built with traditional wall materials (P = 0.050), spending nights with cattle in the same house (P < 0.001), and availability of kitchen in the main house with no partition (P = 0.004) were significantly associated with asymptomatic malaria infection. Conclusions Asymptomatic malaria infection was 4.3 times higher among occupants residing in dwellings built with traditional wall materials; 5.6 times higher among households spending nights with cattle in the same house, and 2.3 times higher among households with kitchen in the main house with no partition. Therefore, policies and strategies on malaria elimination need to address or target improvements of the above listed living conditions for the community. A multi sectoral action is required to use these social determinants as a vector control strategic addition; and malaria elimination programs are expected to coordinate the implementation.